Review of Debussy: Impressionism and Symbolism by Stefan Jarocinski, trans. Rollo Myers and Claude Debussy and the Poets by Arthur B. Wenk - Shepherd, John (Contact: A Journal for Contemporary Music (1971-1990), 1977)
-